Pengembangan Virtual Reality Pengenalan Binatang Buas Untuk Anak Usia Dini - Pradnyana, I Made Ardwi; Arthana, I Ketut Resika; Sastrawan, I Gusti Bagus Hari (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 3 Desember 2017, 2017)
Submission of learning materials with animal themes, especially wild animals to early childhood becomes a challenge for teachers. Two-dimensional displacement media in the form of a monotonous image has the potential to decrease interest in children's learning. Bringing wild animals directly or bringing the children to the zoo requires considerable cost and time and harm. Based on these problems, the authors develop android-based applications that contain fourteen species of wild animals in 3D format that is packed with Virtual Reality (VR) technology. The authors develop applications using development research methods with the ADDIE model. The developed VR application is capable of displaying wild animal animations complete with the sounds and environment of the habitat, as well as the description narrative features and food that can be viewed in 3D and VR modes. The test results showed that the application received a positive response from users, especially children in TK Negeri Pembina Singaraja. The average percentage for the user response test is 88.50%, which means it is very good where children can know the types of wild animals, the movements of wild animals, the sounds of wild animals, the habitats of wild animals and can use them easily.